2011
DOI: 10.1136/oem.2010.059170
|View full text |Cite
|
Sign up to set email alerts
|

School-sponsored work programs: a first look at differences in work and injury outcomes of teens enrolled in school-to-work programs compared to other-working teens

Abstract: SSW programs were created to prepare youth for transition into the workforce after high school. This first study suggests that students in SSW programs working only one job are no more likely to be injured at work compared with other-working teens. However, being enrolled in SSW programs is not protective against work injury, which would have been expected based on the philosophy of these programs. Furthermore, when students work multiple jobs, those enrolled in SSW programs are more likely to be severely inju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…[ 13 ] Moreover, students in CTE programs have been more likely to report having been informed of legal rights and having received safety training than those working outside of these structured programs. [ 14 ] The U.S. Office of Vocational and Adult Education previously estimated, on average, every high school student has taken at least one CTE course, and 1-in-4 students completed three or more courses in a single program area. [ 13 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 13 ] Moreover, students in CTE programs have been more likely to report having been informed of legal rights and having received safety training than those working outside of these structured programs. [ 14 ] The U.S. Office of Vocational and Adult Education previously estimated, on average, every high school student has taken at least one CTE course, and 1-in-4 students completed three or more courses in a single program area. [ 13 ]…”
Section: Introductionmentioning
confidence: 99%
“…This risk remained elevated even after they controlled for hours worked [ 8 ]. Two other recent studies in the United States have also shown an increased risk of injury for MJHs: an elevated rate of work-related fatalities for MJHs was reported in Kentucky, and an elevated rate and severity of injury was reported for adolescent MJHs in Wisconsin [ 11 , 12 ]. This could be due to long work hours, long daily commutes, multiple shifts, and less sleep and leisure time; all factors that may increase the risk of fatigue and injury for MJHs [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple job holders (MJHs), defined as those working more than one job in a one-week period, now make up 10% of the US workforce and are more likely than single job holders (SJHs) to be working in part-time work, work greater than 50 hours a week, as on-call workers or independent contractors, and work the evening shift or other non-regular schedule (Marucci-Wellman et al, 2014 ). Although there has been limited research on the health effects for MJHs, an elevated risk of work-related fatalities was reported in Kentucky (Bush et al, 2013 ), and an elevated risk of work-related injuries to teens working in more than one job was found in Wisconsin (Zierold et al, 2011 ). Additionally, using the US National Health Interview Survey (NHIS) data pooled over 15 years (1997–2011), an elevated risk of work-related injury and non-work-related injury was found for MJHs compared with SJHs, even after controlling for usual weekly work hours (Marucci-Wellman et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%